Human milk oligosaccharide 2'-fucosyllactose promotes melanin degradation via the autophagic AMPK–ULK1 signaling axis - Heo, Hyojin; Cha, Byungsun; Jang, Dongmin; Park, Chaewon; Park, Gunwoo; Kwak, Byeong Mun; Bin, Bum Ho; Park, Ji Hwan; Lee, Mi Gi (Scientific Reports, 2022)
There is still an unmet need for development of safer antimelanogenic or melanin-degrading agents for skin hyperpigmentation, induced by intrinsic or extrinsic factors including aging or ultraviolet irradiation. Owing to the relatively low cytotoxicity compared with other chemical materials, several studies have explored the role of 2'-fucosyllactose (2'-FL), the most dominant component of human milk oligosaccharides. Here, we showed that 2'-FL reduced melanin levels in both melanocytic cells and a human skin equivalent three-dimensional in vitro model. Regarding the cellular and molecular mechanism, 2'-FL induced LC3I conversion into LC3II, an autophagy activation marker, followed by the formation of LC3II+/PMEL+ autophagosomes. Comparative transcriptome analysis provided a comprehensive understanding for the up- and downstream cellular processes and signaling pathways of the AMPK–ULK1 signaling axis triggered by 2'-FL treatment. Moreover, 2'-FL activated the phosphorylation of AMPK at Thr172 and of ULK1 at Ser555, which were readily reversed in the presence of dorsomorphin, a specific AMPK inhibitor, with consequent reduction of the 2'-FL-mediated hypopigmentation. Taken together, these findings demonstrate that 2'-FL promotes melanin degradation by inducing autophagy through the AMPK–ULK1 axis. Hence, 2'-FL may represent a new natural melanin-degrading agent for hyperpigmentation.
Keywords: AMP-Activated Protein Kinases; Autophagy; Autophagy-Related Protein-1 Homolog; Humans; Hyperpigmentation; Intracellular Signaling Peptides and Proteins; Melanins; Milk, Human; Trisaccharides